THE HYPOTHETICAL ACTIVITIES OF TEACHER QUESTIONING IN PROMOTING EFL STUDENTS’ LEARNING - Milawati - Milawati (Premise: Journal of English Education and Applied Linguistics, 2017)
This conceptual paper shares the idea of the hypothetical activities of teacher questioning roles in facilitating EFL students’ learning. Evidence is mounting that teacher questions can assist EFL students in various purposes in teaching learning process. The teacher tends to deliver a simple to complex level of question, in order the discussion can run smoothly. Despite this, a various of good questions will not guarantee that the interactive classroom will be created, the appropriate teacher roles in deploying question is a need.Teachers play different roles when they ask different questions, and these roles affect students’ learning. It can be developed by considering; the contents to be taught, the types of questions to be deployed, the role of teacher to be possed and the tasks chosen. The blueprint of the teacher questioning activities can be used in conducting effective classroom questioning.